Wybrane realizacje sceniczne poznańskich „Łejerów” – refleksja u progu 50-lecia istnienia zespołu - Sadowska, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2025)
Purpose of the study: The study aims to synthetical present the most important stage productions of the Poznań, “Łejery” community on the threshold of the 50th anniversary of its existence. Research methods and research status: The study uses the method of analysing existing and evoked sources, which include: press materials, information obtained by the author during conversations conducted at Primary School No. 83 in Poznań with Jerzy Hamerski and Elżbieta Drygas, electronic sources related to the facility, studies and articles from serial publications and phonographic sources as well as prints obtained from Jerzy Hamerski’s collection. The current state of research on “Łejery” pedagogy is insufficient, because “Łejery” pedagogy, the main pillar of which is education through art, has existed for almost 50 years and is a unique phenomenon in Poland. This phenomenon, thanks to the determination of Jerzy Hamerski and Elżbieta Drygas, resulted in the establishment of Primary School No. 83 in 1990. Emilia Waśniowska in Poznań (although “Łejery” was established as a children’s community theatre in 1975). So far, you can read about the Poznań theater school only in the magazine Kultura i Edukacja from 2024. Conclusions: No random performances or songs are in the “Łejery” repertoire. They refer to current social and educational problems, phenomena worth explaining to children, and, above all, to children’s everyday problems. Many of the stage productions are addressed primarily to adult audiences to draw their attention to a child’s perception of the world.